I Shot the Sheriff, but Only My Analyst Knows: Shrinking the Psychotherapist-Patient Privilege - Domb, Brian (1991)
This Note will discuss the psychotherapist-patient privileges as it relates to past crimes and will use the Menendez facts to analyze different problems associated with the privilege. First, privileges law in general will be described with an emphasis on the public policy rationales supporting the specific privileges; ample space will then be devoted exclusively to the psychotherapist -patient privilege, especially the unique problems associated with having any exceptions which allow testimony of psychotherapeutic communications. The Note will then discuss the recognized exceptions to the psychotherapist privilege to see if a case can be made for an exception relating to past crimes. Empirical studies have shown the futility in using the expectations of a reasonable patient about his or her confidences in determining the reasonableness of an exception to the privilege. Therefore, this Note argues for adoption of a not unreasonable standard in analyzing the psychotherapist-patient privilege exceptions to conclude that courts should define (and legislatures should adopt) clearly worded psychotherapist-patient privilege rules with a homicide exception for past crimes. The current existence of the judicial discretion approach to privilege exception problems underscores the need for clearer and more uniform standards